Thermal annealing effects on vanadium pentoxide xerogel films - G. N. Barbosa (Eclética Química, 2005)
The effect of water molecules on the conductivity and electrochemical properties of vanadium pentoxide xerogel was studied in connection with changes of morphology upon thermal annealing at different temperatures. It was demonstrated that the conductivity was increased for the samples heated at 150oC and 270oC compared to the vanadium pentoxide xerogel. It was also verified a stabilization of electrochemical processes of the insertion and de-insertion of lithium ions the structure of thermally annealed vanadium pentoxide.